Assessing the effects of multichannel service provider corporate reputation on customer new product adoption and RFM value. (10th May 2018) - Walsh, Gianfranco; Schaarschmidt, Mario; Ivens, Stefan
Abstract : Purpose: Service providers leverage their corporate reputation management efforts to increase revenues by shaping customer attitudes and behaviours, yet the effects on customer innovation adoption and customer value remain unclear. In an extended conceptualisation of customer-based corporate reputation (CBR), the purpose of this paper is to propose that customer perceived risk, perceived value, and service separation are contingencies of the relationship between CBR and two key customer outcomes: customer new product adoption proneness (CPA) and recency-frequency-monetary (RFM) value. Design/methodology/approach: Using a predictive survey approach, 1, 001 service customers assess the online or offline operations of six multichannel retailers. The hypothesised model is tested using structural equation modelling and multigroup analysis. Findings: The analysis reveals significant linkages of CBR with perceived risk and perceived value, as well as between perceived risk and perceived value and from perceived value to CPA and RFM value. These linkages vary in strength across unseparated (offline) and separated (online) services. Research limitations/implications: This study uses cross-sectional data to contribute to literature that relates CBR to relevant customer outcomes by considering CPA and RFM value and investigating contingent factors. It provides conceptual and empirical evidence that price appropriateness represents a new CBR dimension. Practical implications: The results reveal that CBR reduces customers' perceived risk and positively affects their perceived value, which drives CPA and RFM value. Multichannel retailers can create rewarding customer relationships by building and nurturing good reputations. Originality/value: This study is the first to link CBR with customer product adoption proneness and value, two important customer measures. It proposes and tests an extended conceptualisation of CBR.